Formulasi Gel Lidah Buaya dan Peppermint Oil untuk Mengurangi Pruritus pada Kasus Gagal Ginjal Kronik - Munjiati Munjiati; Ulfah Agus Sukrilah; Nastiti Nur Indriyani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Patients with advanced-stage kidney disease commonly experience dermatological disorders, with pruritus (itchy skin) being the most prevalent skin manifestation. Other frequent complaints among chronic kidney disease patients include fatigue, muscle weakness, dry skin, and insomnia. Chronic pruritus, or uremic pruritus, is a persistent itching sensation that significantly reduces the quality of life of patients undergoing hemodialysis, affecting over 40% of them. Conventional treatments for uremic pruritus include emollients, topical creams such as capsaicin, ultraviolet B phototherapy, gabapentin, oral activated charcoal, nalfurafine, and opioid antagonists. As a natural alternative, aloe vera and mint have shown potential in relieving skin discomfort due to their soothing, anti-infective, antioxidant, and moisturizing properties. This study aimed to develop a gel formulation containing aloe vera and mint, using peppermint oil, Carbopol 940, triethanolamine, glycerin, methylparaben, and distilled water. Three formulations were prepared with varying concentrations of aloe vera: 10%, 15%, and 20%. The best formulation was F1, containing 10% aloe vera, characterized by a clear gel, a distinctive peppermint aroma, and a homogeneous texture. The formulation had a pH of 6; adhesion time of 7.53 ± 0.261 seconds; spreadability of 6.83 ± 1.04 cm; and viscosity of 5495 ± 83.2 mPas.